THE MEDIATION ROLE OF WELL-BEING STUDENTS ON THE INFLUENCE OF 21st CENTURY COMPETENCE AND BLENDED LEARNING ON ENTREPRENEURSHIP LEARNING ACHIEVEMENT - Ramadhan, Ramadhan; Sofiyan, Sofiyan; Efendi, Efendi; Siregar, Robert Tua; Lie, Darwin (SULTANIST: Jurnal Manajemen dan Keuangan, 2022)
This research uses qualitative descriptive analysis methods and quantitative descriptive analysis. The object of the study of the Private Vocational School for the Preparation of Pematangsiantar City with a sample of 187 respondents. The methods used for data analysis in this study are validity, reliability, normality, multiple and simple linear regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis test (F test and t-test). This can be concluded as follows: 1) The regression analysis results show a positive influence between 21st-century competencies and blended learning on well-being students simultaneously and partially, and there is a positive influence between well-being students and learning achievement. 2) The correlation and determination results show a strong and positive relationship between 21st-century competencies and blended learning with well-being students both simultaneously and partially, and there is a very strong and positive relationship between well-being students and entrepreneurial learning achievements. 3) The simultaneous test results show that the FH 0 test was rejected, meaning that 21st-century competence and blended learning positively and significantly affect students' well-being. 4) The partial test results show that the t H 0test is rejected, which means that 21st-century competence and blended learning have a significant effect on partial well-being students, and the results of the t H 0test are rejected, which means that well-being students have a significant effect on partial entrepreneurial learning achievement